Digitalizing Emergency Response Team Inspection Through Kaizen in a Manufacturing Company - MOHD ARIS, NURFARHANA; BIN JAMIAN, RAHIM (Progress in Engineering Application and Technology, 2025)
This project explores the digitalization of Emergency Response Team (ERT) inspections by applying Kaizen principles in a manufacturing company. Previously, the company utilized a Microsoft Forms-based autonomous inspection checklist, which led to inefficiencies such as prolonged response times, difficulty in tracking historical data, and an increased risk of errors. By the third quarter of 2024, the average response time for completing inspections and reporting findings through the company’s system (SAP) was 10 minutes. The manual process posed challenges, including burdensome categorization, difficulty in retrieval, and unnecessary motion, contributing to longer response times and reduced overall effectiveness. To address these issues, a digital solution was implemented using Kaizen’s continuous improvement principles and Cadence mobile apps for real-time mobile data capture. The transition to a digital inspection process significantly improved efficiency, reduced inspection times, and enhanced the accuracy of reported findings. Real-time data collection facilitated faster responses, streamlined the identification and resolution of safety issues, and minimized disruptions. This approach fostered better adherence to safety protocols, improved interdepartmental teamwork, and enabled quicker decision-making. Additionally, digital records provided valuable insights into safety performance, aiding ongoing improvements. The findings demonstrate the positive impact of digital tools and Kaizen principles in enhancing ERT efficiency through mobile and safety management, resulting in a safer and more responsive manufacturing environment.